Real Effects of Capital Inflows in Emerging Markets - Igan, Deniz (IMF Working Papers; Working Paper ;, 2016)
We examine the association between capital inflows and industry growth in a sample of 22 emerging market economies from 1998 to 2010. We expect more external finance dependent industries in countries that host more capital inflows to grow disproportionately faster. This is indeed the case in the pre-crisis period of 1998-2007, and is driven by debt, rather than equity, inflows. We also observe a reduction in output volatility but this association is more pronounced for equity, rather than debt, inflows. These relationships, however, break down during the crisis, hinting at the importance of an undisrupted global financial system for emerging markets to harness the growth benefits of capital inflows. In line with this observation, we also document that the inflows-growth nexus is stronger in countries with well-functioning banks.